Project Based Learning Dalam Pembelajaran Bahasa Arab di MA Miftahul Falah Bandung - Alamsyah, Firman; Nurkolis Majid, Muhamad; Kosim, Nanang; Lathifah Fauziah, Eva (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
The UN emphasizes the importance of 21st century education in building a knowledge-based society. Learning in this era is influenced by new guidelines from UNESCO, which emphasize four main elements, namely collaboration, communication, creativity and critical thinking (4C). One type of 21st century learning evaluation that can be applied is Project-based learning evaluation. Project-based assessment is a learning activity that involves students in making projects so that learning is centered on students and teachers act as supervisors in the learning process. The purpose of this study was to determine the application of project-based learning evaluation at MA Miftahul Falah. This research is descriptive qualitative research, with data collection techniques of observation and interviews and documentation. The results of this study show that project-based Arabic learning at MA Miftahul Falah for grades 11 IPA and 11 IPS is carried out through several stages, namely project preparation and presentation, discussion, group division, teacher supervision, and presentation of final results. Students are divided into four groups with different themes, namely في سوبرماركت (in the supermarket), في السوق التقليدي (in the traditional market), في قسم الملابس (in the clothing department), and في قسم الفواكه والخضروات (in the fruit and vegetable department). These learning stages include initial learning in the classroom, independent project work outside the classroom, and discussion of project results in the classroom